Determination of Priority Regions as The Direction of Decision-Making for Land Development of West Kalimantan Province - Ratih Fitria Putri; Aryana Rachmad Sulistya (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
Indonesia is an archipelago country consisting of large and small islands with a large number of approximately 17,508. Some of the islands are among the border to neighboring countries. One of the islands is a border area of land that is found on the island of Borneo, especially West Kalimantan Province. West Kalimantan province is directly adjacent to Malaysia. The identic character of the Indonesian border area is largely a lagging region. Determination of priority areas is certainly needed as an effective way of developing these border areas. The objectives of the research include (1) identification of the distribution of lagging priority areas in West Kalimantan Province, (2) give recommendations related to development of lagging priority areas. Overlays of lagging region parameters and economic productivity are used to determine priority areas. The result of identification is known that Bengkayang Regency, Kayong Utara, and Melawi are the lagging priority areas. Recommendation given to the lagging priority regions are through regional development model and also based on determination of base sector.